Rancang Bangun Transportasi Logistik Kakao Agroindustri Coklat Kabupaten Pidie Jaya Provinsi Aceh - Yusriana Yusriana; Rachman Jaya (Agricultural Faculty, 2013)
Factual problems of the cocoa bean agroindustry at Pidie Jaya District, Aceh Province were large distances between farmers and processor, thus determining the shortest part route, backhaul location and quality risk becomes critically to the assess. The objective this research are to determine shortest route based on the location of suppliers, back location, and risk quality recommendations. Requirement of shortest part route solved by Algorithm Djisktra, Backhaul location with MPE and Risk management quality by Multi Expert Multi Criteria Decision Making, aggregation criteria with OWA. The result of the study shows that the shortest distance suppliers Aceh Timur District was 282km, Aceh Utara District 116km, Bireuen District 57km, Pidie District 24km and Aceh Tenggara District 391km. Backhaul location sat Aceh Tengah District with a value of MPE(6533). Alternative of quality risk management were direct fermentation, improvement of transport facilities and container with a high rating criteria, thus the agroindustry has to focus on this dimension.